MYANMAR DAN MATINYA PENEGAKAN DEMOKRASI - Irewati, Awani (Jurnal Penelitian Politik, 2007)
Abstract Democratization in Myanmar is the most prevalent issue for international society The world takes the issue because the country has beenfor decades under authoritarian regime since militaryjunta takeover the government via coup d etat Since 1990 general election which had been won by National League for Democracy NLD the Military Junta Tatmadaw still ruled the country as a sole authoritarian regime Transition to democracy which been pledged by thejunta has not shown any positive outcome The paper is sought to answer two questions base on the actualpolitical circumstance in Myanmar how is theprogress ofdemocratic and human rights enforcement that has been pushed by pro democratic people in Myanmar The second question will bring our attention to the power ofthe prolonged militaryjunta in Myanmar Even though Myanmar has been under economic sanction and isolatedfrom international society there is no evidence that the military junta will come to an end Based on literature study as the main source ofdata collecting approach this paper bringsforward two conclusions Those two conclusions emerge from the existing internal and external political condition ofMyanmar Internal political condition shown that ethnical diversity in Myanmar is main obstaclefor establishing oppositional coalition against the military junta Ethnic in Myanmar is separated in fictionalized movement against the ruling authoritarian regime since colonial era It is still complicated until recent time to build a coalition from pro democratic movement in Myanmar The second conclusion is coming from the international society in putting more pressure towards the ruling regime It is goodfor the UN and the international society notjust isolating and sanctioning Myanmar but also approaching Myanmar using the influence ofthe third country China is good to become a promoter political reformation in Myanmar since China is the only country that still maintains a close relation with Myanmar This approach is to give more emphasis for Myanmar government to comply with its own pledge toward democratic transition in its own country.